Molecular implications of HOX genes targeting multiple signaling pathways in cancer - Shenoy, U Sangeetha; Adiga, Divya; Kabekkodu, Shama Prasada; Hunter, Keith D; Radhakrishnan, Raghu (Cell biology and toxicology, 2022)
Homeobox ( HOX ) genes encode highly conserved homeotic transcription factors that play a crucial role in organogenesis and tissue homeostasis. Their deregulation impacts the function of several regulatory molecules contributing to tumor initiation and progression. A functional bridge exists between altered gene expression of individual HOX genes and tumorigenesis. This review focuses on how deregulation in the HOX-associated signaling pathways contributes to the metastatic progression in cancer. We discuss their functional significance, clinical implications and ascertain their role as a diagnostic and prognostic biomarker in the various cancer types. Besides, the mechanism of understanding the theoretical underpinning that affects HOX -mediated therapy resistance in cancers has been outlined. The knowledge gained shall pave the way for newer insights into the treatment of cancer. Graphical abstract